PENERAPAN BALANCED SCORECARD PADA KOPERASI PETANI SAWIT (KOPSA) USAHA MAJU DESA MEKAR JAYA KECAMATAN KAMPAR KIRI TENGAH KABUPATEN KAMPAR - Madha Lela; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This study aims to find out how the application of the Balanced Scorecard to the Koperasi Petani Sawit (KOPSA) Usaha Maju Desa Mekar Jaya Kecamatan Kampar Kiri Tengah Kabupaten Kampar. The Balanced Scorecard is a tool used to measure the performance of the Koperasi Petani Sawit (KOPSA) Usaha Maju not only from the financial sector but also from the non-financial sector. The data used in this study are secondary data, namely in the form of financial reports and annual members meeting report of the Koperasi Petani Sawit (KOPSA) Usaha Maju Desa Mekar Jaya from 2013 to 2018.Data analysis used is using the Balanced analysis Scorecard with four Balanced Scorecard perspectives. The results of the Balanced Scorecard analysis on each of the four perspectives show that the financial perspective shows a pretty good performance even though the ratio calculation shows fluctuations. From the customer perspective the cooperative's performance in retaining members is quite good, because in the 2013-2018 period no members left the cooperative membership list. The internal business process perspective shows good performance because the credit realization process can run efficiently and in 2017 the Koperasi Petani Sawit (KOPSA) Usaha Maju can establish a new business units. And on the perspective of growth and learning performance is considered quite good, seen from employee retention there are no employees who leave and on employee productivity employees still show productive. Then the results of a comprehensive analysis of the perspective of the performance of the Koperasi Petani Sawit (KOPSA) Usaha Maju Desa Mekar Jaya approved quite well. Keywords: Performance Appraisal, Balanced Scorecard, Cooperatives